After Effects Expressions. - Geduld, Marcus, ....- (Burlington, MA : Focal, 2009)
Description Put the power of Expressions to work in your animations with controls and efficiencies impossible to achieve with traditional keyframing techniques. No programming skills are required. Foundation concepts and skills orient the new designer and serve as a handy reference to the experienced one. Basics of creating Expressions, variables, commands, and Expression helpers precede the leap into JavaScript and math essentials for more advanced Expressions that include randomness and physical simulations. Full color illustrations display the scripts and the resulting effects, Pick Whip techniques, and sequential animations. Downloadable companion files include QuickTime movies of the demo animations, and AE project files that permit you to examine the Expressions. * No programming experience required. * Full-color presentation of Pick Whip techniques and sequential animations. * Downloadable project files and QuickTime videos. Contents Part 1: Using Expressions Creating Simple Expressions Variables, Comments, and Dimensions Commands Expression Helpers Part 2: Foundations for Advanced Expressions JavaScript for Expressions Math Is Your Friend Advanced Techniques Randomness Physical Simulations
Keywords: After Effects Expressions